doaçao Paulo Figeiredo : museu de arte moderna de sao paulo. - Mesquita, Ivo; Chiarelli, Tadeu; Cintrao, Rejane; Fabris, Annateresa; Uchoa Fagundes jr., Carlos Eduardo (Sao Paulo : Museu de Arte Moderna, 2001)
Ceverny, Alex ; Flemming, Alex ; Quentin, Bernard ; Schendel, Mira ; Giannotti, Marco ; Musatti, Jeanete ; Miguez, Fabio ; Kühn, Heinz ; De Souzanetto, Manfredo ; Tozzi, Claudio ; et al.
Tentoonstelling 'Doaçao Paulo Figueiredo', Museu de arte contemporaneo, 2001.
Engels
Portugees
boek